Developing a statistical formula for identifying four-character words in chinese text. - Chua, Hiang Ngee. (2008)
3 new statistical formulas were developed for identifying 4-character words in Chinese text. These formulas were constructed by performing stepwise logistic regression using the same set of data created Dai, Khoo & Loh (1999).